Propriospinal myoclonus: evidence for spinal "pattern" generators in humans. - Brown, P; Rothwell, J; Thompson, P; Marsden, C (1994)
The clinical and electrophysiological characteristics of eight patients with propriospinal myoclonus are described. Myoclonus developed within days or weeks of cervical trauma in half the patients. Seven cases had axial flexion jerks, and one axial extension jerks. Myoclonic EMG activity consisted of repetitive bursts with a frequency of 1-7 Hz. The jerks in three of the cases were comprised of alternating and rhythmic bursts of EMG activity in rectus abdominis and the paraspinal muscles. From these new observations, it is proposed that cervical trauma can lead to the partial release of a spinal pattern generator. The latter is capable of recruiting muscles through long propriospinal pathways into complex rhythmic activity.